2019
DOI: 10.1155/2019/3476347
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Nanofertilizers and Their Application as a Foliar forCucurbita pepoL

Abstract: The implementation of nanofertilizers in agriculture is the purpose in specific to decrease mineral losses in fertilizing and raises the yield during mineral management as well as supporting agriculture development. Hence, this experiment was conducted in Shebin El-Kom, El-Monifia governorate, Egypt, during two seasons 2017 and 2018 to study the effect of micronutrient oxide nanoparticles of zinc, iron, and manganese, as well as combination between these oxides as a foliar application on the growth, yield, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(29 citation statements)
references
References 43 publications
(48 reference statements)
1
23
0
Order By: Relevance
“…21 Manganese is also a micronutrient used in acidic soil, 22 but its use as nano-Mn 3 O 4 has been limited. Recently, nano-Mn 3 O 4 was applied to leaves by spraying a suspension of 20 mg/L, after 20 days from the sowing of the seeds of squash plants until 40 days from sowing, 23 improving the growth plant yield but decreasing the yield of fruit. Another study reported that nano-Mn 2 O 3 applied at 6 mg/kg/plant promoted nutrient fixation in wheat, but it was found that manganese could affect plants in subtle ways when applied in soil rather than via foliar.…”
Section: ■ Introductionmentioning
confidence: 99%
“…21 Manganese is also a micronutrient used in acidic soil, 22 but its use as nano-Mn 3 O 4 has been limited. Recently, nano-Mn 3 O 4 was applied to leaves by spraying a suspension of 20 mg/L, after 20 days from the sowing of the seeds of squash plants until 40 days from sowing, 23 improving the growth plant yield but decreasing the yield of fruit. Another study reported that nano-Mn 2 O 3 applied at 6 mg/kg/plant promoted nutrient fixation in wheat, but it was found that manganese could affect plants in subtle ways when applied in soil rather than via foliar.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hence, bioinspired synthesis of nanofertilizers will be a key not only in decreasing the cost of production and making the production safe, but it also influences the growth at a much higher pace. The reason behind their biocompatibility which has no toxic impacts on plants and slow-release with the passage of time which allows the plants to utilize them properly [ 38 , 39 ]. However, the negative influence at higher concentration might be due to the accumulation of NRs around the shoots or extensive release of iron which negatively impact the growth like iron salt [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Shebl et al [43] have synthesized zinc, manganese, and iron nanooxides via a green chemistry technique using a microwave-assisted hydrothermal method weight in maize plantlets indicating that these can be used as micronutrient nanofertilizer [44]. Open Journal of Ecology…”
Section: Nanofertilizersmentioning
confidence: 99%